High-throughput single-cell chromatin accessibility CRISPR screens enable unbiased identification of regulatory networks in cancer - Sarah E. Pierce (Nature Portfolio, 2021)
Transcription factor binding dynamics can drive epigenetic states, enabling a diversity of phenotypes. Here the authors present Spear-ATAC to quantify and map perturbations to chromatin accessibility in single cells at high throughput.